(untitled) (Al-Farooq Journal of Sciences, 2026)
This study examines how a promotional advertisement for Seacoast International School’s Ain Zara branch constructs persuasive appeal and reproduces ideological assumptions about international schooling. Using Fairclough’s three-dimensional model of critical discourse analysis, using qualitative textual analysis, the transcript is examined at the textual, discursive, and social levels. Textually, superlative comparison, antithetical slogans, unmodalized predictive claims, and direct address through "we," "you," and "your child" construct the advertisement’s persuasive force. Discursively, the advertisement borrows legitimacy from an internationally distributed curriculum and predominantly foreign teaching staff rather than local evidence of quality, positioning parents as decision-makers responsible for a child’s future opportunity. At the social level, these choices reflect a neoliberal reframing of education as a competitive, internationally benchmarked investment rather than a public good, treating English proficiency and foreign instruction as prerequisites for success. The findings extend Fairclough’s account of marketized discourse in public higher education to a private, multilingual K-6 context, showing how the advertisement naturalizes a hierarchy of educational value without stating it directly.